The Vascular Arrangement and Main Branches of Arteria Axillaris in Wing of Sparrowhawk (Accipiter nisus) - BALKAYA, H.; OZUDOGRU, Z.; OZDEMIR, D.; CAN, M.; ERBAS, E.; KARA, H. (Journal of the Hellenic Veterinary Medical Society, 2018)
This study was aimed to determine the vascular arrangement of the wing arteries in the sparrowhawk. For this purpose, wing arteries of eight sparrowhawks were assessed by latex injection method and angiography. Latex injection method was applying to the five materials and barium sulphate solution was injected for angiography in other three materials. It was observed that the arterial blood was mainly provided to the wing by arteria axillaris. The arteria axillaris gave off arteria subscapularis. After branching the arteria subscapularis, it emitted the arteria profunda brachii and arteria supracoracoidea. After ramifying these vessel, the arteria axillaris continued down arteria brachialis. This vessel was giving off the arteria circumflexa humeri from its cranial aspect. In the nearby the cubital fossa the arteria brachialis bifurcated arteria ulnaris and arteria radialis. The arteria ulnaris gave off common stem of arteria recurrens ulnaris et arteria ulnaris profunda. After branching the common stem, the arteria ulnaris proceeded as arteria ulnaris superficialis. The arteria radialis was the deep terminate branch of the arteria brachialis. This vessel bifurcated the arteria radialis profunda and arteria radialis superficialis.